2010
DOI: 10.1007/s10546-010-9494-z
|View full text |Cite
|
Sign up to set email alerts
|

Can Water Vapour Raman Lidar Resolve Profiles of Turbulent Variables in the Convective Boundary Layer?

Abstract: High-resolution water vapour measurements made by the Atmospheric Radiation Measurement (ARM) Raman lidar operated at the Southern Great Plains Climate Research Facility site near Lamont, Oklahoma, U.S.A. are presented. Using a 2-h measurement period for the convective boundary layer (CBL) on 13 September 2005, with temporal and spatial resolutions of 10 s and 75 m, respectively, spectral and autocovariance analyses of water vapour mixing ratio time series are performed. It is demonstrated that the major part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 66 publications
9
113
0
Order By: Relevance
“…Increasing water vapour variance upwards in this layer produces the observed patterns of refractive change during the day. Observations (Wulfmeyer et al 2010) and modelling (Stull 1988) elsewhere indicate that upward-increasing variance of specific vapour humidity in the mixed layer is to be expected, which is consistent with our observations. Paths to the ground surface above 800 m a.s.l.…”
Section: Summary and Fit To The Ablsupporting
confidence: 92%
See 1 more Smart Citation
“…Increasing water vapour variance upwards in this layer produces the observed patterns of refractive change during the day. Observations (Wulfmeyer et al 2010) and modelling (Stull 1988) elsewhere indicate that upward-increasing variance of specific vapour humidity in the mixed layer is to be expected, which is consistent with our observations. Paths to the ground surface above 800 m a.s.l.…”
Section: Summary and Fit To The Ablsupporting
confidence: 92%
“…To the upper right is a profile of the specific humidity through the daytime ABL based on the BOMEX results (Siebesma et al 2003), which can be regarded as the baseline ocean ABL state for the atmosphere around Montserrat. The variance of the specific humidity is shown schematically (no units) based on observations and modelling (Stull 1988;Wulfmeyer et al 2010). This shows very high levels of specific humidity variance around the entrainment layer falling to much lower levels at the base of the mixed layer lines of evidence to properly parameterise the degree of turbulence of the ABL layers.…”
Section: Summary and Fit To The Ablmentioning
confidence: 99%
“…The agreement between the airborne and ground lidar flux profiles is fairly good. A recent study with another ground-based water vapour Raman lidar corroborates our finding that profiles of turbulent variables in the CBL can in principal be obtained with such systems (Wulfmeyer et al, 2010).…”
Section: Fluxes Over the Rhine Valleysupporting
confidence: 87%
“…Remote sensing techniques overcome these limitations and cover larger ranges simultaneously and continuously. Monitoring moisture fluctuations with high resolution for turbulence studies is a challenging task due to the noise limitation of these instruments; nevertheless, new techniques based on lidar are capable of providing data with sufficient precision and accuracy Wulfmeyer et al 2010Wulfmeyer et al , 2015. Couvreux et al (2005) compared the results of airborne water vapour DIAL measurements from the IHOP campaign with LES for a growing CBL.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas it is also possible to derive higher-order moments with water vapour Raman lidar, Wulfmeyer et al (2010) and Turner et al (2014) demonstrated that the noise level in daytime turbulence profiles is much larger than for water vapour DIAL. Therefore, water vapour Raman lidar turbulence profiles are strongly limited to measurements of third-and fourth-order moments.…”
Section: Introductionmentioning
confidence: 99%